Ifugao bulubunduking buhay - Corre, Fruto; Rodrigo, Nancy Pe (Bookmark, 1998)
This documentary shows how the payos or rice terraces of the Ifugao were built, as well as the beliefs, legends, traditions and art that were inspired by the terraces. It also features the three remaining mumbakis of the Ifugaos, and the Hudhud, an Ifugao harvest song.